Blacksmith and Blacksmithing Attributes in Folklore of Tungus-Manchurian Peoples of Russian Far East - Л. Е. Fetisova (Научный диалог, 2023)
The article is devoted to the peculiarities of the perception of blacksmiths and blacksmithing by the folklore consciousness of the indigenous ethnic groups of the southern part of the Russian Far East — the Nanais, Orochs, Ulchis, Negidals, Udeges, Oroks (Uilta) of Sakhalin, who are considered to be distant descendants of the Mohe and Jurchens. The novelty of the study lies in the fact that for the first time from the general array of the narrative folklore of the Tungus-speaking peoples, texts were singled out, where the central character is an anthropomorphic character, in the guise of which the main tools of blacksmithing are presented: a head-hammer, a chest — blacksmith furs, legs-skewers, hands ticks. The study showed that in the oral work of the Far Eastern aborigines, iron and craft attributes often received a negative assessment; the magical properties attributed to the blacksmith were transferred to iron products and tools of his labor, represented by images of cannibalistic monsters. At the same time, the masters themselves could remain positive heroes, endowed with the features of a demiurge. At the same time, the masters themselves could remain positive heroes, endowed with the features of a demiurge. It is concluded that the anthropomorphization of blacksmith tools is a representative element of the plot, widespread among the Far Eastern Tungus-Manchus, but unknown to the Nivkhs.